An Unusual Presentation of Lipoma on the Dorsum of the Foot in A 9 Year Old Girl: A Case Report and Review of the Literature - Chika, Agu Thaddeus (Archives of Clinical and Medical Case Reports, 2017)
A lipoma can occur in virtually any organ of the body that has fat cells. A slow growing mass on the dorsum of the foot in a 9 year old girl which had recently ulcerated and was painful appeared sinister. In the absence of trauma or local scarification on the mass, the spontaneous denudation of the overlying skin and eventual ulceration with discharge of serous fluid seemingly made malignancy a probable but not a definite diagnosis. The groin nodes were enlarged and tender but there was no cough and no weight loss. Biopsy confirmed the diagnosis of lipoma. The aim of this report is to highlight the need for the clinician to be broad minded in the management of patients and to consider the psychological impact of making a pronouncement without a confirmatory diagnosis.